Quantitative ultrasound imaging reveals distinct fracture-associated differences in tibial intracortical pore morphology and viscoelastic properties in aged individuals with and without diabetes mellitus – an exploratory study - Dehnen, Carolin; Galindo, Angela; Hoff, Paula; Palme, Oliver; Maurer, Lukas; Raum, Kay; Wiebe, Edgar (Frontiers in Endocrinology, 2024)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disorder that increases fragility fracture risk. Conventional DXA-based areal bone mineral density (aBMD) assessments often underestimate this risk. Cortical Backscatter (CortBS) ultrasound, a radiation-free technique, non-invasively analyzes cortical bone's viscoelastic and microstructural properties. This study aimed to evaluate CortBS's discriminative performance in DM patients compared to DXA and characterize changes in cortical bone microstructure in Type 1 and Type 2 DM (T1DM, T2DM) patients.Methods: This in-vivo study included 89 DM patients (T1DM = 39, T2DM = 48) and 76 age-and sex-matched controls. DXA measured aBMD, while CortBS measurements were taken at the anteromedial tibia using a medical ultrasound scanner with custom software. Multivariate analysis of variance assessed the impact of DM type on CortBS and DXA measurement results. Partial least squares discriminant analyses with cross-validation were used to compare the discrimination performance for vertebral, non-vertebral, and any fragility fractures, adjusting for gender, age, and anthropometric parameters (weight, height, BMI).Results: Fractures occurred in 8/23 T1DM, 17/18 T2DM, and 16/55 controls. DXA parameters were reduced in fracture patients, with significant diabetes impact. T2DM was associated with altered CortBS parameters, reduced scatterer density, and larger pores. CortBS outperformed DXA in discriminating fracture risk (0.61 ≤ AUC(DXA) ≤ 0.63, 0.68 ≤ AUC(CortBS) ≤ 0.69).Conclusions: Both T1DM and T2DM showed altered bone metabolism, with T2DM linked to impaired tissue formation. CortBS provides insights into pathophysiological changes in diabetic bone and provided superior fracture risk assessment in DM patients compared to DXA.